Innovation Prosperity Index and its Impact on a Country’s Capacity Management - DANKO, T.P.; CHAYKOVSKAYA, L. A.; KISELEV, V.M.; SOLOVYOVA, M.G.; NEDELKIN, A.A.; RAUSKIENE, Ona; SEKERIN, V.D. (Journal of Advanced Research in Law and Economics, 2019)
This research analyzes the issues of the positioning of Russia in relation to four countries selected for the study: Germany, Spain, Portugal and Greece. Using the Prosperity/Innovation Index developed by the Legatum Institute, which is formed under the influence of various factors, and the economic-mathematical apparatus and statistical methods, a forecast model has been built that can be used with a sufficient degree of reliability to assess the dynamics of development in the future.